Rancang Bangun Sistem Kendali Pintu Pagar Otomatis Berbasis Pengolahan Citra Digital Pelat Nomor Kendaraan Menggunakan Metode Optical Character Recognition (OCR) - Syah Alam; Firman Fauzi; Gunawan Tjahjadi; Ridzki Saputro Sya’ban (Faktor Exacta, 2022)
The gate is the main access to enter and exit the vehicle. In general, the gate is opened and closed manually by humans so it takes time and effort. This study proposes the design of an automatic gate control system based on digital image processing of vehicle number plates using the Optical Character Recognition (OCR) method to be able to recognize vehicle number plates. The vehicle number plate image will be recorded by a USB camera and processed using MATLAB to recognize each character on the vehicle number plate. Then the results of processing the vehicle number plate image are compared with the number plate database that has been inputted into the system. If the number plate is registered in the database, MATLAB will forward the command to Arduino Uno to drive the servo motor to open the gate. From the test results, it takes 7 seconds to process the vehicle number plate image processing until the gate is open. The percentage of successful reading of vehicle number plate characters by the MATLAB system is 100% of the 6 number plates tested with an accuracy of 100%. This research can be recommended as an automatic gate control system for security in buildings and homes.